1996
DOI: 10.1046/j.1365-2141.1996.d01-1470.x
|View full text |Cite
|
Sign up to set email alerts
|

Soluble interleukin‐6 receptor as a prognostic factor in multiple myeloma

Abstract: Interleukin-6 (IL-6) is a major growth factor for the clonal malignant plasma cells in multiple myeloma (MM). The effect of IL-6 may be enhanced by soluble IL-6 receptor (sIL-6R). As there is a clinical need for improved stratification of MM patients at diagnosis, we have studied the role of sIL-6R as a prognostic marker in 207 newly diagnosed MM patients. Serum sIL-6R concentration was above the upper reference limit in 47% of the patients at diagnosis. The concentrations of sIL-6R and two other prognostic fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0
4

Year Published

1997
1997
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(47 citation statements)
references
References 16 publications
(33 reference statements)
4
39
0
4
Order By: Relevance
“…(2) A second was reported that patients with raised levels of both sILpossible mechanism for the decrease of the serum sIL-6R 6R and ␤2-microglobulin had shorter survival than other level is a consumption of circulating sIL-6R due to formapatient groups indicating its prognostic value for the tion of IL-6/sIL-6R complexes in the presence of IL-6 and stratification of patients. 36 subsequent binding and internalization of the complexes by In the present work, we show an increase of serum ILtarget cells expressing the gp130 signal transducing protein. 6 during the aplastic phase after bone marrow or peripheral Circulating IL-6/sIL-6R complexes are found in patient blood stem cell transplantation culminating at day 6 folsera, 13,31 and it has been reported that IL-6 can down-regulowed by a decrease to baseline values.…”
Section: Patientssupporting
confidence: 62%
“…(2) A second was reported that patients with raised levels of both sILpossible mechanism for the decrease of the serum sIL-6R 6R and ␤2-microglobulin had shorter survival than other level is a consumption of circulating sIL-6R due to formapatient groups indicating its prognostic value for the tion of IL-6/sIL-6R complexes in the presence of IL-6 and stratification of patients. 36 subsequent binding and internalization of the complexes by In the present work, we show an increase of serum ILtarget cells expressing the gp130 signal transducing protein. 6 during the aplastic phase after bone marrow or peripheral Circulating IL-6/sIL-6R complexes are found in patient blood stem cell transplantation culminating at day 6 folsera, 13,31 and it has been reported that IL-6 can down-regulowed by a decrease to baseline values.…”
Section: Patientssupporting
confidence: 62%
“…For myeloma it is well known that interleukin-6 (IL-6) plays a crucial role in the cytokine network, regulating the growth and survival of myeloma cells and stimulating the acute-phase protein synthesis, notably C-reactive protein (CRP) (Lauta, 2003). Several authors investigating serum IL-6 in relation to acute-phase reactants and survival in myeloma patients report not only significantly shorter survival for those with higher concentrations of IL-6 compared with patients who had normal concentrations (Ludwig et al, 1991;Pulkki et al, 1996;Papadaki et al, 1997;Stasi et al, 1998), but also demonstrate a strong positive correlation between IL-6 and CRP (Tienhaara et al, 1994;Pelliniemi et al, 1995;Kyriakou et al, 1997;Biro et al, 1998;Alexandrakis et al, 2003). As an assessment of infection status at the time of surgery was made, CRP rather appears to act as a surrogate marker for IL-6 activity and proliferative status of bone marrow plasma cells and has been regarded as a powerful prognostic marker in patients with multiple myeloma, than a sign for preoperative infectious states.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated serum IL-6 receptor concentrations are associated with a poor prognosis in MM and used as an indicator of disease activity. 59 Other cytokines, including TNFa, have been reported to be involved in the control of VEGF production by myeloma cells. 60 Moreover, VEGF directly, or indirectly through its stimulatory activity on TNF-a and Il-b1 stimulates the activation of osteoclasts and thus contributes to the lytic lesions in MM.…”
Section: Vegf In Multiple Myeloma R Ria Et Almentioning
confidence: 99%